An East Indian home, Trinidad - (:unkn) unknown (My University, 2010)
An East Indian family outside an ajoupa or tapia hut. The walls of these huts are usually made from a mixture of clay, grass, cow dung and water, while the roof is usually made from carat or palm leaves.
Colour: Black and white; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Huts--Trinidad and Tobago; Housing--Trinidad and Tobago; East Indians--Trinidad and Tobago; Rural families--Trinidad and Tobago; Dwellings--Trinidad and Tobago; Ajoupa